Predicting related factors of immunological response to hepatitis B vaccine in hemodialysis patients based on integration of decision tree classification and logistic regression - Yongliang Feng; Jianmin Wang; Zhihong Shao; Zhuanzhuan Chen; Tian Yao; Shuang Dong; Yuanting Wu; Xiaohong Shi; Jing Shi; Guangming Liu; Jingen Bai; Hongping Guo; et al. (Taylor & Francis Group, 2021)
The non/hypo-response rate of the hepatitis B vaccine among hemodialysis (HD) patients is still high, it is of great significance to explore the influencing factors and their relationships. To study the related factors and their relationships using logistic regression model and Chi-squared Automatic Interaction Detection (CHAID) decision tree model. A randomized controlled trial was conducted between February 2014 and May 2015 in China. HD patients being serologically negative for HBsAg and anti-HBs were randomly assigned to receive three intramuscular injections of the standard dose (20 µg) or high dose (60 µg) of recombinant hepatitis B vaccine at months 0, 1, and 6. Those with anti-HBs concentrations <100 mIU/mL, and ≥100 mIU/mL at month 7 were considered as non/hypo-response and high-level response, respectively. The non/hypo-response was 31.34% (89/284). After adjustment for confounders, logistic analysis showed that males (OR = 2.203, 95%CI: 1.109-4.367) and those with higher dialysis frequency (>4 times per 2 weeks) (OR = 1.918, 95%CI: 1.015-3.626) had a significant risk of non/hypo-response. While the CHAID analysis showed that gender, dose, and dialysis frequency were influencing factors of non/hypo-response, and gender is most important. The interaction between gender and dialysis frequency had the greatest effect on immunization, and followed by the interaction between dialysis frequency and vaccine dose. Taken together, gender, dose and dialysis frequency were influencing factors of hepatitis B vaccine in HD patients.